ISOLATION AND IDENTIFICATION OF ENDOPHYTIC BACTERIA FROM ROOTS AND STEMS OF GREEN BETEL PLANT (PIPER BETLE L.) AND EVALUATION OF THEIR ANTIBACTERIAL ACTIVITY - Ringga Novelni (Jurnal Kesehatan Medika Saintika, 2025)
The green betel plant (Piper betle L.) is known to possess antibacterial activity due to its secondary metabolite content, such as tannins, saponins, flavonoids, terpenoids, polyphenols, and steroids. This study aims to determine the characteristics and antibacterial activity of endophytic bacteria isolated from the roots of the green betel plant (Piper betle L.) against Staphylococcus aureus and Escherichia coli. The research employed an experimental method involving bacterial isolation, macroscopic and microscopic identification, as well as antibacterial activity testing of the endophytic bacteria against S. aureus and E. coli using the Kirby-Bauer disk diffusion method. Furthermore, molecular identification of the endophytic bacteria was conducted using the 16S rRNA gene through the Polymerase Chain Reaction (PCR) method. The macroscopic morphological characteristics of the isolated endophytic bacteria showed round, flat-raised colonies with curved edges and a clear white appearance. Microscopic observation through Gram staining revealed that the bacteria were rod-shaped (bacilli) and Gram-positive. The antibacterial activity test showed that the isolate produced an inhibition zone of 11.45 mm against Staphylococcus aureus, which is categorized as weak and indicates that the bacteria have a narrow-spectrum antibacterial effect. Meanwhile, no antibacterial activity was observed against Escherichia coli. It can be concluded that the pure isolates of endophytic bacteria from the roots and stems of the green betel plant belong to the Gram-positive group and exhibit antibacterial activity only against Staphylococcus aureus with a weak inhibitoryeffect